Analysis of Policy and Politics in Education within Medical Education Programs at Private Universities in Indonesia - Katuuk, Deitje Adolfin; Suprapto, Denny U.; Lapian, Jeff; Pali, Nathaniel E.; Palandeng, Rian W. (International Journal of Information Technology and Education, 2025)
Medical education in Indonesia has experienced rapid development, marked by an increasing number of private universities opening medical study programs. However, this dynamic is inseparable from the influence of national policies and higher education politics. This article analyzes how national policies and political dynamics affect the existence, quality, and governance of medical education in private universities. The approach used is policy document analysis and literature review. The results show that government regulations, particularly Law No. 20/2003, Law No. 12/2012, and Minister of Health Regulation No. 24/2020, play a significant role in the establishment and development of medical study programs. However, political pressure, institutional competition, and higher education liberalization pose challenges to graduate quality and equitable access. Recommendations include enforcing quality standards, strengthening the accreditation system, and collaborative governance between the state and private institutions.